2019
DOI: 10.1111/hae.13853
|View full text |Cite
|
Sign up to set email alerts
|

BAY 94‐9027 prophylaxis is efficacious and well tolerated for up to >5 years with extended dosing intervals: PROTECT VIII extension interim results

Abstract: Introduction: BAY 94-9027 is an extended-half-life, site-specifically PEGylated, Bdomain-deleted recombinant factor VIII (FVIII). The PROTECT VIII main study demonstrated efficacy of bleed control using extended-interval prophylaxis with BAY 94-9027 for 36 weeks. Aim: To report long-term efficacy and safety of prophylaxis with BAY 94-9027 in a descriptive analysis of the ongoing PROTECT VIII extension with a total treatment time of up to >5 years. Methods: Previously treated males aged 12-65 years with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
(39 reference statements)
3
30
0
1
Order By: Relevance
“…A second distribution compartment could not be identified for damoctocog alfa pegol (CV on Q = 103%); the PK of damoctocog alfa pegol was adequately described by a onecompartment model (technically, the PK of damoctocog alfa pegol was described by a two-compartment model fixing Q to a very small value [0.001]), while a two-compartment model was used for rurioctocog alfa pegol. Compared with damoctocog alfa pegol, the CL of rurioctocog alfa pegol was significantly increased by 21% (95% CI, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This effect was consistent across patients with an estimated betweenpatient variability of 11.5% CV and 17 out of 18 patients having a CL value in favor of damoctocog alfa pegol compared with rurioctocog alfa pegol, respectively.…”
Section: Population Pk Modeling and Time To Threshold Simulationmentioning
confidence: 83%
See 1 more Smart Citation
“…A second distribution compartment could not be identified for damoctocog alfa pegol (CV on Q = 103%); the PK of damoctocog alfa pegol was adequately described by a onecompartment model (technically, the PK of damoctocog alfa pegol was described by a two-compartment model fixing Q to a very small value [0.001]), while a two-compartment model was used for rurioctocog alfa pegol. Compared with damoctocog alfa pegol, the CL of rurioctocog alfa pegol was significantly increased by 21% (95% CI, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This effect was consistent across patients with an estimated betweenpatient variability of 11.5% CV and 17 out of 18 patients having a CL value in favor of damoctocog alfa pegol compared with rurioctocog alfa pegol, respectively.…”
Section: Population Pk Modeling and Time To Threshold Simulationmentioning
confidence: 83%
“…Rurioctocog alfa pegol is a full-length rFVIII product that has been PEGylated at its B-domain, with a branched 20-kDa PEG molecule (Advate®; Baxter, USA) [12,13]. Rurioctocog alfa pegol was first licensed in 2015, and damoctocog alfa pegol in 2018, for the treatment of hemophilia A, based on efficacy and safety data from their respective pivotal phase 2/3 clinical trials [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 126 patients who completed the main study, 121 entered the extension that confirmed the safety and efficacy of BAY 94-9027 prophylaxis with dosing intervals of up to every 7 days for >5 years 9. Given the importance of preventing joint damage for patients with severe haemophilia A, we performed a post hoc analysis on…”
mentioning
confidence: 99%
“…A total of 107 subjects completed the extension study, receiving prophylaxis with BAY 94-9027 (twice weekly, n ¼ 23; 5 days, n ¼ 33; 7 days, n ¼ 23; variable frequency, n ¼ 28). 34 The overall FVIII consumption in the prophylaxis group was 290 IU/kg/month, 326 in the twice-weekly arm, 290 in the 5-day arm, and 260 in the 7-day arm. The median ABR in the overall prophylaxis group was 1.6, with 21% of subjects reporting zero bleeding episode.…”
Section: Resultsmentioning
confidence: 92%